Sifat Organoleptik Nasi Goreng Hongkong Instan dengan Variasi Substitusi Sawut Singkong - Dewi, Mustika Amira Luthfiana; Sri Handajani; Ila Huda Puspita; Lilis Suliandari (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
The high consumption of rice and the continuous increase in rice prices in Indonesia have encouraged the development of healthier alternative foods. This study aims to evaluate the organoleptic properties of instant Hong Kong fried rice with grated cassava (sawut singkong) substitution as a rice replacement. An experimental method was used with substitution variations of 40%, 50%, and 60%. The main ingredients included rice, white cassava, vegetables, fried rice seasoning, and other complementary ingredients. The preparation process involved ingredient preparation, boiling, steaming, frying, freezing, and drying. Organoleptic tests were conducted to assess the product’s appearance, color, aroma, taste, texture, and overall preference in both dry and rehydrated forms. The results showed that the 50% cassava substitution product was the most preferred by the panelists in terms of color, taste, aroma, appearance, texture, and overall acceptability. This product is considered to have potential as a high-fiber instant food and supports food diversification efforts.